PENERAPAN STRATEGI LIPIRTUP BERBASIS MEDIA FILM INSPIRATIF SEKOLAH RIMBA DALAM MENINGKATKAN KETERAMPILAN MENULIS CERPEN SISWA KELAS V SD NEGERI 22 KALUKUE KABUPATEN PANGKEP - Nurhikmah, Syarifah; Bahri, Aliem; Rahayu, Sri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low short story writing skills of fifth-grade students at SD Negeri 22 Kalukue. The problems identified included students’ difficulties in developing ideas into coherent and meaningful stories, as well as the use of conventional teaching methods that did not sufficiently encourage creativity. The research employed a Classroom Action Research (CAR) design conducted in two cycles. The subjects of the study consisted of 20 fifth-grade students. Data were collected through observation, short story writing tests, and documentation. The findings revealed a significant improvement from one cycle to the next. In Cycle I, the learning mastery level reached only 40%, with the average score not yet meeting the Minimum Learning Achievement Criteria (KKTP). After improvements were implemented in Cycle II, the mastery percentage increased to 95%. The 55% increase indicates that the Lipirtup strategy (See, Choose, Reflect, Express, and Publish) based on inspirational film media was effective in enhancing students’ motivation, active participation, and ability to compose short stories systematically, coherently, and creatively.